Analysis of students' mathematical communication ability in solving STEM-based mathematics problems by gender of class VII students of SMPN 02 Ambulu, Jember district - Wahyuni, Indah; Faizah, Dwi Nisafatul (SAINTIS Publishing, 2024)
This research is motivated by public perceptions about the ability to solve math problems in male and female students. One of the abilities assessed for differences is mathematical communication ability. This study aims to describe mathematical communication skills in solving STEM-based math problems in class VII students of SMPN 02 Ambulu. The subjects chosen were 6 students consisting of male and female students with high, medium, and low mathematical communication abilities. This research is a descriptive study with data collection techniques: Observation, Tests, Interviews, Documentation. Data analysis refers to Miles and Huberman, namely, Data Condensation, Data Presentation and Conclusion Drawing. The research results obtained for male and female students with high mathematical communication skills showed no difference, LT and PT students were able to fulfill the same indicators of mathematical communication ability, as well as male and female students who had low mathematical communication abilities, their mathematical communication skills are the same. However, students with moderate communication skills have differences in indicators.